The Story of Polish “Orientalness” – Researching Islam in Poland - Rak , Karolina (KnE Social Sciences, 2019)
Polish academia has a long tradition of studies on the Middle East, Islam and its heritage. Oriental studies have been part of university curricula in Kraków, Lvov (today in Ukraine) and Vilno (today Vilnius is the capital of Lithuania), later expanding also in such cities as today’s capital Warsaw [1]. The Oriental studies concentrated on the MiddleEastduetocontactsPolandhashadwiththeregion.Oneofthemostinteresting ideas brought up by researchers is based on the observations of cultural encounters throughout the turbulent history of the country leading some to coin terms such as Polish “Orientalness”. This term denotes a set of identity and cultural characteristics and can beopposed to the widely debated “Orientalism”, as deﬁned by the renowned Palestinian intellectual and academic Edward Said in his seminal book from 1979, due to different experiences of relations with Muslim communities. Today’s Poland due to several, mainly historical factors, is one of the most homogenous nations of the entire world so it seems crucial to look upon patterns of multicultural existence which were once experienced on a daily basis. Keywords: Orientalness, Islam, Poland, borderland